ÙØ¹Ø§Ù„ÙŠØ© Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØµÙˆØªÙŠØ© "Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨ÙŠÙ† ÙŠØ¯ÙŠÙƒ" Ù„ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ø¯Ø±Ø§Ø³Ø© ÙƒÙ…ÙŠØ© ÙÙŠ Ø¯ÙˆØ±Ø© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¹Ø¨Ø± Ø§Ù„Ø§Ù†ØªØ±Ù†Øª ÙÙŠ Ø§Ù„Ø£Ø²Ù‡Ø§Ø± ÙƒØ§Ø¯ÙŠØ±ÙŠ - Yustika Hardianti; Lailatul Qomariyah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2021)
This article examines the effectiveness of the use of learning media "Audio Al Arabiyah Baina Yadaik in improving speaking skills in Al Azhar online arabic courses. This research aims to; (1) Knowing the use of learning media "Audio Al Arabiyah Baina Yadaik; (2) Knowing the learning of speaking skills; (3) Knowing the effectiveness of the use of learning media "Audio Al Arabiyah Baina Yadaik in improving speaking skills. Researchers used quantitative methods with tests, interviews and observations, then analyzed using the Man Whitney Test. The results of the research: (1) The use of audio learning media in Al Azhar online Arabic Course consists of two types: al arabiyah baina yadaik audio media as the main subject and audio media containing explanations from teachers. (2) Arabic language learning in Al Azhar Kediri Arabic Course consists of two parts, namely: offline learning and online learning. (3) Al Arabiyah Baina Yadaik's audio media is effective for improving speaking skills. This is indicated by the test result of man withney test with a Sig value, 0.011 < 0.005. Keywords: Learning Media, Arabiyyah Baina Yadaik